Comparative ex vivo Investigations on the Cutting Quality of the CO2 Laser and the Diode Pumped Er:YAG Laser - Wurm, Holger; Schuler, Patrick Johannes; Hausladen, Florian; Graesslin, René; Hoffmann, Thomas Karl; Stock, Karl; Reins, Elisabeth Friederike (Frontiers in Surgery, 2021)
Objectives: A sufficient histological evaluation is a key pillar in oncological treatment, especially in situations of cancer of unknown primary. CO2 laser technology is used in clinical routine of soft tissue surgery because of its cutting quality and availability. Diode pumped solid state Er(bium):YAG laser systems promise a higher cutting efficiency and minor thermal damages. The aim of this study was to compare both laser systems with respect to their suitability for cutting soft tissue. Methods: A setup was realized which enables comparable experiments with the clinical CO2 laser (AcuPulse 40ST DUO, Lumenis) and the Er:YAG laser system (DPM 40, Pantec Biosolutions AG). Fresh mucosal samples of porcine tongues were used to determine the influence of laser power and sample velocity on cutting depth and thermal damage width for both lasers. In addition, for the Er:YAG laser, the influence of the pulse repetition rate was examined additionally. For analysis, images of histological sections were taken. Results: In all experiments, the Er:YAG laser shows a significantly higher cutting depth (P < 0.0001) and less thermal damage width (P < 0.0001) than the CO2 laser. For example, at an average power of 7.7 W and a sample velocity of 5 mm/s the Er:YAG laser shows a mean cutting depth of 1.1 mm compared to the CO2 laser with 500 μm. While the Er:YAG laser shows a mean thermal damage width of 70 μm compared to 120 μm. Furthermore, the Er:YAG enables the adjustment of the cutting depth and thermal damage width by varying the irradiation parameters. A decrease of the repetition rate leads to a reduction of thermal damage. For example, a repetition rate of 100 Hz results in a thermal damage width of 46 μm compared to 87 μm at 800 Hz at an average power of 7.7 W and a cutting velocity = 5 mm/s while a homogenous cutting quality can be achieved. Conclusions: In conclusion, the results of these ex vivo experiments demonstrate significant advantages of the diode pumped Er:YAG laser system for soft tissue ablation compared to the CO2 laser, in particular regarding cutting efficiency and thermal damage width.